Sign Changing Solutions for Coupled Critical Elliptic Equations. (11th February 2020) - Wang, Xin; Yue, Xiaorui
Abstract : In this paper, we consider the coupled elliptic system with a Sobolev critical exponent. We show the existence of a sign changing solution for problem P for the coupling parameter − μ 1 μ 2 < β < 0 . We also construct multiple sign changing solutions for the symmetric case.